Apologies Repair Trust via Perceived Trustworthiness and Negative Emotions - Ma, Fengling; Wylie, Breanne E.; Luo, Xianming; He, Zhenfen; Jiang, Rong; Zhang, Yuling; Xu, Fen; Evans, Angela D. (Frontiers in Psychology, 2019)
The present study examined whether perceptions of a transgressor’s trustworthiness mediates the relationship between apologies and repaired trust, and the moderating role of negative emotions within this process. Chinese undergraduate students (N= 221) completed a trust game where they invested tokens in their counterpart, and either experienced no trust violation (i.e., half of the tokens returned), a trust violation (i.e., no tokens returned), or a trust violation followed by an apology. Participant’s trust behavior was measured by the number of tokens they re-invested in their counterpart in a second round of the game. Participants also completed measures to assess perceptions of the transgressor’s trustworthiness and emotional state. Results revealed that participants who received an apology were more likely to trust in their counterpart, compared to those who did not receive an apology, and this relationship was mediated by perceptions of the transgressor’s trustworthiness. Further, the relationship between apologies and perceptions of the transgressors trustworthiness was moderated by negative emotions; apologies only improved perceptions of trustworthiness for participants who experienced less negative emotions.